PENGARUH NILAI TUKAR RUPIAH, HARGA INTERNASIONAL DAN JUMLAH PRODUKSI KAKAO TERHADAP VOLUME EKSPOR KAKAO INDONESIA - Putri, Annisa; Juanda, Reza (Jurnal Ekonomi Pertanian Unimal, 2024)
This research aims to determine the effect of the rupiah exchange rate, international prices, and the amount of cocoa production on the volume of Indonesian cocoa exports from 1990-2022. This research uses secondary data and time series data from 1990-2022 obtained from the World Bank, Badan Pusat Statistic (BPS), and International Cocoa Organizations. The data analysis method uses the Autoregressive Distributed Lag (ARDL) approach. The results of this research show that the rupiah exchange rate variable in both the short and long term has a positive and insignificant effect on the volume of Indonesian cocoa exports. In the short term, the international cocoa price variable has a positive and insignificant effect on the volume of Indonesian cocoa exports, while in the long term, it has a negative and insignificant effect. And the production quantity variable has a positive and significant impact on the volume of Indonesian cocoa exports in the short and long term.